Anxiety Disorders Among Cancer Patients: An Observational Study - Bal Shashi Sinha; Dr. Nisha Sisodia; Dr. Pranab Kumar Chakraborty; Dr. Anil Aggarwal; Dr. Bimlendu Kumar Roy (The Bioscan, 2026)
Anxiety disorders represent a significant yet often underrecognized psychological comorbidity among cancer patients. This review summarizes recent data on the epidemiology, etiology, presentation and treatment of ADs in patients with cancer. Based on analyses of observational studies and literature from current patients, this review shows that anxiety disorders affect 20-50% of patients with cancer at different stages and types. The multidimensional order of cancer-related anxiety includes diagnosis, treatment regimen, prognosis and individual psychological variables leading to thorough assessment and specific intervention approach. Both cognitive-behavioral therapy, pharmacological treatments, and comprehensive interventions are found to be effective in reducing SAD symptoms. This article suggests that routine screening and early intervention of anxiety disorders should be part of standard cancer care which could lead to improved quality of life, as well as increased compliance with treatment and success in the outcome.